1992
DOI: 10.1159/000111655
|View full text |Cite
|
Sign up to set email alerts
|

Functional Capacities of Transplanted Cell-Sorted Adult Oligodendrocytes

Abstract: Previous work has shown that transplanted dissociated glial cells derived from neonatal rats can myelinate areas of the myelin deficient (md) rat spinal cord. In the present studies we have examined the ability of adult glial cells, either as suspension of mixed glial cells or as 01 positive oligodendrocytes purified by cell sorting, to myelinate md rat axons following transplantation. Mixed glial cell preparations from adult rats myelinated large areas of either, dorsal, lateral or ventral columns. These area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Multiple approaches have been developed for OPC purification; each has its own merits. Compared to other OPC isolation methods such as costly immunopanning 5,9,10 and technically demanding differential gradient centrifugation 7,8,12 , the method for OPC preparation through oligosphere generation from both mouse and rat neural progenitor cells is simple and straightforward 20,21,26 . It can be easily followed by a researcher without prior OPC isolation experience.…”
Section: Anticipated Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple approaches have been developed for OPC purification; each has its own merits. Compared to other OPC isolation methods such as costly immunopanning 5,9,10 and technically demanding differential gradient centrifugation 7,8,12 , the method for OPC preparation through oligosphere generation from both mouse and rat neural progenitor cells is simple and straightforward 20,21,26 . It can be easily followed by a researcher without prior OPC isolation experience.…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…These include proliferating OPCs, characterized by expression of progenitor cell markers such as the platelet-derived growth factor alpha receptor (PDGFaR) with a bipolar or tripoIar morphology, intermediate immature oligodendrocytes, expressing markers recognized by the O4 antibody with a multipolar morphology, and finally mature myelinating oligodendrocytes, expressing myelinspecific proteins such as myelin basic protein. When transplanted into the brain of hypomyelinated hosts, oligodendrocyte precursors can migrate a significant distance, and give rise to a large number of mature oligodendrocytes 6,7 , as well as myelinate axons 8 . Simple methods for the isolation and purification of workable quantities of OPCs not only aid in efforts to better understand oligodendrocyte development, function and axonoligodendroglial interactions but also provide an indispensable tool for myelin repair research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of transplanted glial cells to ensheath axons and synthesize myelin when transplanted into dysmyelinating mutants or chemically created models of demyelination has been studied extensively (1)(2)(3)(4)(5)(6). Until now the primary assay of myelin-forming grafts has of necessity been anatomical rather than functional or electrophysiological.…”
mentioning
confidence: 99%
“…Although some studies have suggested that mature differentiated oligodendrocytes are useful myelinating cells, 10 the majority view is that mitotic 65 and migratory 14,66,67 capacities are vital prerequisites for successful remyelination, and that postmitotic oligodendrocytes, lacking these competencies, do not readily recapitulate their development to form myelin sheaths again. 14,68,69 Despite their motility, oligodendrocyte progenitors show poor survival and migration when implanted into normal white matter, although they are able to populate and remyelinate when injected into, or very close to, lesioned tissue.…”
Section: Choice Of Reparative Cellmentioning
confidence: 99%